Volumetric Absorptive Microsampling (VAMS) technology for IGF-1 quantification by automated chemiluminescent immunoassay in dried blood. (February 2020) - Marchand, A.; Roulland, I.; Semence, F.; Audran, M.
Abstract: For medical diagnostics and anti-doping analyses, insulin-like growth factor 1 (IGF-1) can be measured in serum using automated chemiluminescent immunoassays. The aim of this study was to assess the feasibility of using dried blood instead of serum to measure IGF-1 concentrations with an automated IGF-1 immunoassay and to evaluate if IGF-1 concentrations from dried capillary blood and serum were comparable. Blood samples (venous blood and capillary blood obtained from the arm skin using a device from Seventh Sense Biosystem) were collected with 20 μL Volumetric Absorptive Micro samplers (VAMS) (Mitra®, Neoteryx). These samplers offer the possibility of collecting a fixed volume of blood without perturbation by hematocrit. Starting from dried blood, an aqueous desorption in 0.9% NaCl was efficient to release IGF-1. The solution was directly analyzed on the automated IGF-1 immunoassay. IGF-1 concentrations after extraction from VAMS were lower than in serum (due to the dilution performed for the elution of IGF-1) but measurable for serum concentrations over 50 ng/mL. In addition, IGF-1 on VAMS was stable for at least one month at room temperature. Following adjustment for dilution, serum and dried blood IGF-1 concentrations were of the same order. However lower concentrations were obtained from the capillary blood in particular for high serum concentrations. In conclusion, a micro volume of dried capillary blood could be used to quantify IGF-1 with an automated chemiluminescent immunoassay. However, more data are needed to establish specific IGF-1 reference concentrations using dried capillary blood instead of serum. Graphical abstract: Unlabelled Image Highlights: IGF-1 can be quantified from 20 μl of dried blood with IDS-IGF-1 immunoassay. IGF-1 is stable on VAMS for at least 1 month at room temperature. Dilution-adjusted dried capillary blood IGF-1 and serum IGF-1 are of the same order. Dried blood on VAMS slightly underestimated high IGF-1 concentrations.